Diagnostic and clinical considerations in prolonged grief disorder - Maercker, Andreas (Les Laboratoires Servier, 2012)
This review focuses on the similarities and differences between prolonged grief disorder (PGD) and post-traumatic stress disorder (PTSD). It highlights how a PTSD-related understanding aids the investigation and clinical management of PGD. Grief has long been understood as a natural response to bereavement, as serious psychological and physiological stress has been regarded as a potential outcome of extreme or traumatic stress. PTSD was first included in DSM-III in 1980. In the mid-1980s, the first systematic investigation began into whether there is an extreme or pathological form of mourning. Meanwhile, there is much research literature on complicated, traumatic, or prolonged grief This literature is reviewed in this article, with the following questions: Is it possible to distinguish normal from non-normal grief? Which clinical presentation does PGD have—and how does this compare with PTSD? Finally, diagnostic, preventive, and therapeutic approaches and existing tools are presented.